Long term stability of atomic time scales. (5th March 2015) - Petit, G.; Arias, F.
Abstract: We review the stability and accuracy achieved by the reference atomic time scales TAI and TT(BIPM). We show that they presently are in the low 10 −16 in relative value, based on the performance of primary standards, of the ensemble time scale and of the time transfer techniques. We consider how the 1 × 10 −16 value could be reached or superseded and which are the present limitations to attain this goal.